Common Variable Immunodeficiency-Associated Inflammatory Enteropathy: The New Era of Biological Therapy - Arieira,Cátia (2018)
Common variable immunodeficiency (CVID) is the most frequent form of immunodeficiency in adults. Clinical manifestations are heterogeneous with an increased susceptibility to infections and inflammatory conditions, namely autoimmune diseases, such as inflammatory bowel disease. We present the clinical case of a Caucasian female patient, 21 years old, with a past medical history of CVID, with multiple visits to the emergency department due to abdominal pain in the lower quadrants and diarrhea. Her biochemical analysis showed elevated inflammatory parameters. Stool cultures and parasitological examination of feces were negative. Ileocolonoscopy revealed lymphoid nodular hyperplasia of the terminal ileum, and the small bowel capsule endoscopy demonstrated edema and multiple pleomorphic ulcers (Lewis score = 1,104). CVID-associated inflammatory enteropathy was suspected. Budesonide 9 mg/day was started, but no positive clinical response was observed. It was decided to initiate biological therapy with infliximab. The patients condition is currently clinically improved with no complications due to biological therapy.